A comparison of energy recovery from MSW through plasma gasification and entrained flow gasification. (December 2017) - Mazzoni, Luca; Almazrouei, Manar; Ghenai, Chaouki; Janajreh, Isam
Abstract: This work presents a comparison between two thermochemical conversion pathways for energy recovery from waste, entrained flow, and plasma gasification. The software Aspen Plus was used to build two equilibrium models to simulate the behavior of the two gasification processes when the feedstock consists of hand sorted municipal solid waste (MSW) with medium-high heating value. The impact of various level of air oxygen enrichment is investigated by comparing side-to-side the performance of the two processes in terms of syngas composition, syngas lower heating value and cold gas efficiency (CGE). As the results suggest, plasma gasification, with a maximum CGE of 74.8% can be considered a better option than entrained flow gasification with a CGE of 71.6%.